An investigation on SWAAT and electrochemical corrosion behaviour of roll-bonded and brazed aluminium alloy - AA4045/AA3003 - Moema Joseph; Siyasiya Charles; Morudu Veronica; Hadebe Nomsombuluko; Buthelezi Thokozani (MATEC Web of Conferences, 2023)
The formation of Mn/Fe-containing precipitates during a high-temperature treatment known as homogenization is important for the downstream performance of AA3xxx aluminium alloys. There is currently a significant scientific and industrial interest in the use of Al-Si-Mn-Fe sheet alloys in automotive applications to reduce the weight of vehicles. This work is concerned with the precipitation of dispersoids, which occurs over several hours during heating and holding at the homogenization temperature. In this study, therefore, the effects of isothermal soaking time on the microstructure of AA3003 cladded with AA-045 alloy were investigated. The microstructures and intermetallic phases were analysed using optical microscopy (OM) and scanning electron microscopy (SEM). The seawater acetic acid test (SWAAT) and electrochemical corrosion test were used for studying the corrosion behaviour of the AA4045/AA3003 cladded alloy. The results on the effect of soaking time on both microstructure and corrosion properties of the brazed alloy are presented. The OM results show that the microstructure of these alloys consisted of an Al-Si eutectic phase at the surface of the residual clad and a thick diffusion zone which is a band of dense precipitates ( BDP) between the clad and core. The sheet surface reveals the presence of pitting corrosion on the coupons exposed for 30 days and more. The polarization curves of the corrosion tests show that the AA4045/3003 is susceptible to intergranular corrosion (IGC) as a consequence of the higher amount of grain boundary precipitates formed during the brazing process.